Reproduction pattern of â€œgading starlingâ€ (Turdus sp.) at Mount Lawu, Central Java - AGUNG BUDIHARJO (Society for Indonesian Biodiversity, 2005)
The aim of the research was to know reproduction pattern of â€œgading starlingâ€ (Turdus sp.) in natural habitat, namely Mount Lawu. This research was expected to give accurate information that can be used as base of conservation effort. Research had been done alongside of Cemoro Sewu tracking line. Data was collected at 2600, 2800, 3000, 3100, and 3200 m. asl., in March, April, May, and October 2004. Nesting observation was concerning with nest place at tree, height of ground surface, apart from tracking line, nest materials, size and shape of nest. Egg observation was concerning with the amount of egg per nest, time lay eggs, and amount of infant. Environmental data was concerning with air temperature and humidity. The result indicated that nest location had similar type, i.e. located among ramification encircled by some small stick and shaded by leaves. Height of nest about 0.2-7 m above ground surface. About 90% nest was laid in radius less than 40 m of tracking line. Nest materials predominated by grasses mixtured with dry leaf and small stick. Shape of nest was bowl-like with external diameter 16-19 cm and internal diameter 8-12 cm, and deepness of nest 5-7 cm. Breeding season was around March-April. Shape of egg was oval with mean of length 2.4 cm and diameter 1.5 cm. Egg color was pale blue with small pock of pale brown. Mean of egg amount 2-3 items per nest. Mean of efficacy hatch 1-2 individual per nest, but infant which living on generally only 1 individual. During research noted that lowest temperature 80oC, highest temperature 20oC, and mean of air humidity 70-90%. This research concluded that â€œgading starlingâ€ had typical reproduction behavior, especially in selecting nest location and nest materials.Key words: â€œgading starlingâ€, Turdus sp., mount Lawu, reproduction.